PENGARUH PENGGUNAAN MEDIA VISUAL GRAFIS FULL IMAGE AND COLOUR TERHADAP HASIL BELAJAR MEMAHAMI PRINSIP PEMBUATAN MASTER REKAMAN SISWA KELAS X TAV DI SMK NEGERI 2 SOLOK - Aryo Widityo Prabowo; Dharma Liza Said; Ahmaddul Hadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This study was conducted with the low background of student learning outcomes (of the 57 people who completed only 30 people, the remaining 27 have not reached the KKM is 70. Which affecting low learning outcomes one of which is due to the use of the media as a learning the theory process that does not fit. To see the effect of the use of instructional media with Media Visual Graphic full image and color , the research conducted in the form of experiments using with Media Visual Graphic full image and color. experimental type of research with Quasi exsperimental design shape design . study population was all class X TAV Academic Year 2012/2013 which amounts to 57 students in SMK Negeri 2 Solok . sampling technique used non - probability sampling , to sample class X TAV 1 totaled 28 people used the experimental class and class X TAV 2 classes totaling 29 persons used as controls . Results of experimental research using the media class with Media Visual Graphic full image and color has an average value ( 77.39 ) is higher than the control class that does not use with the Media Visual Graphic full image and color of ( 70.68 ) . Keywords : Learning Outcomes , Media , Media Visual Graphic full image and color